Determinants of Health Workers' Performance in Tackling Rubella KLB in Kuantan Singingi District - Citra Iskandar; Hetty Ismainar; Kiswanto; Endang Purnawati Rahayu; Yesica Devis; Musfardi Rustam (Viva Medika, 2024)
Health workers play a key role in handling outbreaks, with performance influenced by factors such as ability, discipline, experience, perception, motivation, leadership support, and appreciation. Despite efforts, basic immunization coverage in recent years has not met the national target of 95%, underscoring the need for optimal health worker performance to achieve coverage goals, control rubella outbreaks, and protect vulnerable groups. This study, conducted at Sentajo and Perhentian Luas Health Centers from January to May 2024, analyzed factors affecting health worker performance in managing rubella outbreaks using a sample of 85 respondents and multivariate regression analysis. The findings indicated that awards (r = 0.377, P = 0.000), motivation (r = 0.336, P = 0.002), ability (r = 0.345, P = 0.000), and work experience (r = 0.302, P = 0.005) significantly influenced performance, with awards having the strongest impact. Conversely, leadership support, discipline, and perception had no significant effect on performance. Based on these results, the Kuantan Singingi District Health Office is advised to implement effective reward policies, such as performance bonuses and certificates of achievement, to boost health worker motivation and performance in handling rubella outbreaks. Enhancing health worker skills and rewarding good performance at the health centers can also help improve immunization rates and community protection against rubella. This approach could serve as a model for other health institutions aiming to increase immunization coverage and disease prevention efforts.